New Techniques in Archaeology - Rainey, Froelich
radiocarbon method; potassium-argon, rubidium-strontium, uranium and lead isotope ratio methods; thermoluminescence technique; radioactive fission-track dating; neutron activation analysis; resistance apparatus; proton magnetometer; cesium magnetometer; underwater archaeology. — “I think most of us are concerned about a better understanding between humanists and scientists in this strange new world of rapid change. There can be no doubt that such understanding develops most readily through daily collaboration in the laboratory and in the field”.